Gender, law, and resistance in India - Moore, Erin P. (Univ. of Arizona Press, 1998)
Gender, Law, and Resistance in India dramatically illustrates how a patriarchal ideology is upheld and reinforced through male-governed social and legal institutions and how women defy that control. Ultimately an account of cultural hegemony and defiance, Gender, Law, and Resistance in India reveals how so-called "modern" state institutions and practices reinforce traditional arrangements, resulting in women being silenced, deprived of equal rights before the law, and returned to their male guardians. Still, women resist in overt and covert ways. The first ethnographic work to focus principally on the law and legal institutions of gender and agency in South Asia, this unique volume examines the interpenetrations of north India's pluralistic legal systems. Moore adeptly connects engrossing case histories to the national dialogues over women's rights, discussing these issues in terms of Muslim personal laws, secularism, and communal violence. Gender, Law, and Resistance in India is a significant contribution to gender studies, South Asian studies, and sociolegal studies.